THE INFLUENCE OF SIMPLE IUD INSERTION TEACHING AIDS ON THE CLINICAL SKILLS OF FOURTH SEMESTER STUDENT AT POLTEKKES KEMENKES MEDAN BACHELOR PROGRAM OF APPLIED MIDWIFERY IN 2025: PENGARUH ALAT PERAGA PEMASANGAN AKDR SEDERHANA TERHADAP KETERAMPILAN MAHASISWI SEMESTER IV SARJANA TERAPAN KEBIDANAN POLTEKKES KEMENKES MEDAN TAHUN 2025 - grevani_marsela br_tarigan; Betty Mangkuji Betty (Colostrum Jurnal Kebidanan, 2026)
Clinical skills are essential competencies in midwifery education. Limited availability of teaching aids in laboratories may hinder optimal skill acquisition among students. Therefore, simple teaching aid innovations are needed as effective learning media. To determine the effect of a simple IUD insertion teaching aid on midwifery students’ clinical skills. This study used a quantitative quasi-experimental design with a one-group pretest-posttest approach. A total of 33 students were selected using systematic random sampling. Skills were measured before and after the intervention using an observation checklist. Data were analyzed using univariate and bivariate analysis with a significance level of 0.05. Before the intervention, most students had moderate skills (±60%), which increased to good category (±75%) after the intervention. Statistical analysis showed a significant difference (p < 0.05). The use of a simple IUD insertion teaching aid significantly improves midwifery students’ clinical skills.